Peran Guru Dan Orang Tua Dalam Membentuk Kecintaan Anak Usia Dini Terhadap Al-Qur’an Di Era Globalisasi - Dewi, Chandra (Prodi PIAUD STAI Sumatera Medan, 2024)
This study aims to analyze the role of teachers and parents in fostering early childhood love for the Qur’an in the era of globalization, with a case study conducted at RA Muslimat NU Gunungsitoli. Using a qualitative method with a case study approach, this research involved interviews, observations, and documentation with teachers, the principal, and parents of students. The findings reveal that children’s love for the Qur’an is developed through synergistic collaboration between teachers and parents, encompassing habituation, exemplary behavior, and the creation of a Qur’an-friendly environment. Teachers act as facilitators of values and spiritual role models through contextual learning and the use of Islamic digital media, while parents serve as reinforcers of Qur’anic values through home-based guidance. Globalization serves as a double edged factor: presenting challenges in the form of digital distractions while also offering opportunities through interactive technology-based learning media. Effective collaboration between teachers and parents is realized through regular communication, joint Qur’an activities, and educational use of technology. This study emphasizes that children’s love for the Qur’an is not an instant outcome but an integrative process between home and school education that adapts to global challenges. The findings provide both theoretical and practical contributions to the development of early childhood Qur’anic education models in Indonesian Islamic institutions.